Twisted penta‐Carbazole/Benzophenone Hybrid Compound as Multifunctional Organic Host, Dopant or Non‐doped Emitter for Highly Efficient Solution‐Processed Delayed Fluorescence OLEDs. Issue 3 (22nd January 2018) - Wang, Fangfang; Cao, Xudong; Mei, Ling; Zhang, Xinwen; Hu, Jia; Tao, Youtian
Abstract : A new multi‐functional penta‐carbazole/benzophenone hybrid compound 5CzBP was designed and synthesized through a simple one‐step catalyst‐free C—N coupling reaction by using 2, 3, 4, 5, 6‐pentafluorobenzophenone and carbazole as starting materials. 5CzBP is very soluble in tetrahydrofuran (THF), which brings an environmentally friendly device fabrication for solution‐processed OLEDs instead of most widely used chlorinated solvents when 5CzBP is employed as the bulk‐phase of organic host or non‐doped emitter in the emissive layer. 5CzBP exhibits thermally activated delayed fluorescence (TADF) characteristic with relatively high triplet energy of 2.60 eV and a low Δ E ST of 0.01 eV. By using the new TADF material as organic host for another green TADF emitter, maximum external quantum efficiency (EQE) of 12.5% has been achieved in simple solution‐processed OLED device. Besides, a maximum EQE of 8.9% and 5.7% was further obtained in TADF devices based on 5CzBP as dopant and non‐doped emitter, respectively. The simultaneously acting as efficient TADF host and non‐doped TADF emitter provides the potential guidance of the future simple single‐layer two‐color white OLEDs based on low‐cost pure organic TADF materials. Abstract : Multifunctional penta‐carbazole/benzophenone hybrid compound 5CzBP was used as organic host, dopant and non‐doped emitter for simple solution‐processed thermally activated delayed fluorescence OLEDs and achieved high maximum EQE of 12.5%, 8.9% and 5.7%, respectively.